Diagnostik und Therapie von Irisläsionen - Mor, Joel M.; Koch, Konrad R.; Heindl, Ludwig M. (Augenheilkunde up2date, 2017)
Teil des klinisch-ophthalmologischen Alltags ist die korrekte Diagnose tumoröser Irisläsionen. Insbesondere die Differenzialdiagnose und die Bewertung der Dignität anhand der Morphologie gestalten sich dabei oft schwierig. Dieser Beitrag gibt einen Überblick über das breite Spektrum von Iristumoren einschließlich empfohlener Diagnostik- und Therapiemodalitäten.The most common iris lesions are iris nevi, iris melanomas and iris pigment epithelium cysts. However, there is an abundance of rare differential diagnoses that have to be considered, including other melanocytic and non-melanocytic lesions. Diagnostic tools include the slit lamp examination, gonioscopy, tonometry, transillumination, ultrasound biomicroscopy (UBM), optical coherence tomography, fluorescein angiography and standardized photography-assisted documentation. The timely identification of malignant lesions (i.e. iris melanoma) is paramount. To assess malignancy criteria of iris nevi, the ABCDEF rule (age young, blood, clock hour inferior, diffuse growth, ektropion uveae, feathery margins) can be applied. Statistically, up to 11% of iris nevi may develop into iris melanomas within 20 years. TNM Staging follows the 2010 AJCC cancer staging manual and helps determine the optimal treatment strategy. Treatment options include radiotherapy, such as plaque brachytherapy and proton beam radiation therapy, as well as surgical excision. Both the surgical and the radiotherapeutic approaches show comparable local tumor control rates. However, the spectrum of therapy-related side effects and complications may differ amongst treatment modalities. After initial treatment, patients should be followed up every 3 – 6 months. Tumor-related mortality ranges between 0 – 11% and is significantly lower than in other uveal melanomas. A prognostic value of common genetic alterations, which have been identified as significant prognostic factors in posterior uveal melanoma, could not be shown for iris melanoma.
Keywords: Iris; Nävus; Melanom; Zyste; Tumor